A PRAGMATIC ANALYSIS: IMPOLITENESS STRATEGY IN FAST X MOVIE (2023) - Permata, Amelia; Wardina, Aqilah Balqis; Azriel G., Putu Rafli; Pamungkas, Rayhan Ramadhanu; Pinshella Amri, Shaqila Filly (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study examines the use of impoliteness strategies in the film Fast X (2023) by analyzing how characters employ language to express conflict, power, and social tension. While language generally functions to maintain harmony and build relationships, real-life communication often includes moments where speakers violate politeness norms, intentionally or unintentionally threatening another person’s social image. To understand these dynamics, this research applies Culpeper’s (2005) impoliteness framework, supported by recent developments in impoliteness studies, to identify and classify instances of face-threatening behaviour in the film. Using a qualitative descriptive method by Creswell & Creswell (2017), the analysis focuses on selected dialogues that demonstrate explicit forms of verbal aggression, such as positive impoliteness, negative impoliteness, sarcasm or mock politeness, bald on-record impoliteness, and withhold politeness. Findings aim to show how impoliteness in cinematic dialogue contributes not only to character development and narrative conflict but also reflects broader patterns of human interaction where dominance, resistance, and emotional intensity shape communication. This study is expected to enrich pragmatic research on film language and to help future researchers on analyzing impoliteness strategies.